The speciﬁc features of cytokine proﬁle of patients with bronchial asthma in an acute stage - N. Yu. Anisimova; Yu. M. Dolzhikova; D. V. Kokushkov; T. V. Borisova; I. O. Chikileva; S. I. Sokurenko; M. V. Kiselevsky; A. V. Karaulov (Сеченовский вестник, 2011)
The aim of this research is to investigate the features of staphylococcal microﬂora of sportsmen of diﬀerent specializations.